ANALISIS PROMOSI DARI MULUT KE MULUT, CITRA MEREK DAN KUALITAS JASA PENGARUHNYA TERHADAP KEPUTUSAN MEMILIH PELATIHAN PRAKERJA DI PINTARIA - Andika Rohani; Lucy Nancy Simatupang; GL. Hery Prasetya (Jurnal Manajemen, 2022)
This study aims to determine the influence of word-of-mouth promotion, brand image and service quality on the decision to choosing the training of prakerja at Pintaria. The population in this study were all Prakerja participants of Pintaria. The sample in this study amounted to 50 respondents. The design used in this study is a Causal. The method used in this study is a quantitative method and the result of the study are based on respondent answer using the Likert Scale. The data analysis method used in this research is Multiple Linear Regression Test, F Test, t Test and Coefficient of Determination with the help of SPSS 24. The result showed that simultaneously (F Test) there was a significant effect between the variables Word-Of-Mouth Promotion (X1), Brand Image (X2), and Service Quality (X3) on decision to choosing (Y). Partially (t Test) Word-Of-Mouth Promotion (X1) has a significant effect on decision to choosing, and Service Quality (X3) has a significant effect on decision to choosing, while Brand Image (X2) has no effect and is not significant to decision to choosing (Y).